(untitled) (The Research of Medical Science Review, 2025)
Background: Sodium-glucose cotransporter-2 (SGLT2) inhibitors are commonly used in managing type 2 diabetes mellitus. While effective, these medications lead to glycosuria (glucose in the urine), which may contribute to an increased risk of urinary tract infections (UTIs). This potential side effect is still seen as a limiting factor in the broader use of these drugs. Objective: This study aimed to evaluate how frequently UTIs occur in individuals with type 2 diabetes who are being treated with SGLT2 inhibitors. Study design: Cross-sectional study Setting: Department of Medicine, Ghulam Muhammad Mahar Medical College (GMMMC) Hospital, Sukkur Study duration: Six months (June 1, 2024 - November 30, 2024) Sampling technique: Non-probability consecutive sampling Sample size: A total of 215 patients diagnosed with type 2 diabetes and receiving SGLT2 inhibitors Patients & Methods: Patients aged between 18 and 75 years with a confirmed diagnosis of type II diabetes and currently on SGLT2 inhibitors were enrolled, regardless of gender. Each participant was assessed for signs and symptoms of urinary tract infection. Collected data were analyzed using descriptive statistics, including means with standard deviations for continuous variables and frequencies with percentages for categorical variables. Results: Out of 215 participants, 130 individuals (60.4%) were found to have a urinary tract infection. The average age was 58.95 years (±10.47 SD). UTIs showed significant associations with several variables, including age (p=0.05), gender (p=0.04), place of residence (p=0.01), presence of hypertension (p=0.04), educational background (p=0.04), symptoms (p<0.01), smoking status (p=0.04), obesity (p<0.01), glycemic control (p<0.01), and marital status (p=0.03). Breakdown of characteristics among the participants were as Gender: 57.7% female, 42.3% male; residence: 40.5% urban, 59.5% rural; education: 23.7% illiterate, 18.6% primary, 18.6% middle, 21.4% secondary, 17.7% higher education; smoking status: 20.5% current smokers, 42.3% ex-smokers; symptoms: Painful urination (29.3%), burning sensation (23.7%), frequent urination (47.0%); obesity present in 53.0%; marital status: Married (24.7%), single (24.2%), separated (26.0%), divorced (25.1%); occupation, housewives (30.2%), employed (27.0%), unemployed (24.2%), business owners (18.6%); uncontrolled diabetes: 61.4% had poor glycemic control Conclusion: The study found a high occurrence of urinary tract infections among type 2 diabetic patients using SGLT2 inhibitors, indicating a need for careful monitoring and preventive strategies when prescribing these medications.